2020
DOI: 10.3390/ijms21218410
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and Calcium Signaling—A Crosstalk for Neuronal Physiology and Pathology

Abstract: Ketamine is a non-competitive antagonist of NMDA (N-methyl-D-aspartate) receptor, which has been in clinical practice for over a half century. Despite recent data suggesting its harmful side effects, such as neuronal loss, synapse dysfunction or disturbed neural network formation, the drug is still applied in veterinary medicine and specialist anesthesia. Several lines of evidence indicate that structural and functional abnormalities in the nervous system caused by ketamine are crosslinked with the imbalanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 162 publications
(211 reference statements)
1
21
0
Order By: Relevance
“…Excessive activation of the excitatory glutamate pathway by methoxphenidine administration would increase calcium influx, resulting in an increase in calcium‐related kinases, such as CAMK2 and PKC. This is consistent with previous studies that have shown that administration of dissociative drug increases these kinases (Lisek et al, 2020; Strong et al, 2017), which are closely involved in the phosphorylation of DAT (Foster & Vaughan, 2017). DAT acts as a reuptake transporter that removes excess dopamine from the synaptic cleft, whereas p‐DAT acts as an efflux transporter that increases dopamine into the synaptic cleft.…”
Section: Discussionsupporting
confidence: 93%
“…Excessive activation of the excitatory glutamate pathway by methoxphenidine administration would increase calcium influx, resulting in an increase in calcium‐related kinases, such as CAMK2 and PKC. This is consistent with previous studies that have shown that administration of dissociative drug increases these kinases (Lisek et al, 2020; Strong et al, 2017), which are closely involved in the phosphorylation of DAT (Foster & Vaughan, 2017). DAT acts as a reuptake transporter that removes excess dopamine from the synaptic cleft, whereas p‐DAT acts as an efflux transporter that increases dopamine into the synaptic cleft.…”
Section: Discussionsupporting
confidence: 93%
“…Ketamine not only significantly inhibited platelet aggregation on the construct surface but also inhibited their activation within the surrounding platelet suspension, as demonstrated by the aggregation state of platelets before and after exposure to the TEML ( Figure 6 II). This is likely due to the known effect of ketamine inhibiting platelet Ca 2+ signalling [ 34 , 35 ]. This would prevent dense granule secretion, which would in turn prevent the activation of these cells in the perfused platelet suspension.…”
Section: Resultsmentioning
confidence: 99%
“…The downregulation of PMCA4 by ketamine was seen in both the GFP and PMCA2b-GFP groups, suggesting a mechanism independent of the presence of PMCA2b. Possible explanations may be the ketamine-mediated generation of reactive oxygen species (Behrens et al, 2007 ) targeting PMCA4-rich lipid rafts, attenuation of c-Fos and c-Jun expression, and subsequent inhibition of AP-1 transcription factor (Lerea et al, 1992 ; Lisek et al, 2020 ), or the involvement of calcineurin, which was previously demonstrated during maturation of cerebellar granule cells (Guerini et al, 2000 ). Interestingly, our data did not show neuronal retraction or changes in the level of differentiation markers in the presence of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Increased apoptotic death was demonstrated to coincide with suppression of spontaneous oscillatory activity and irreversible loss of intracellular Ca 2+ homeostasis (Sinner et al, 2011 ). An increasing body of evidence further supports the calcium hypothesis of ketamine neurotoxicity, suggesting several potential compensatory mechanisms that may lead to the accumulation of intracellular Ca 2+ to potentially toxic concentrations (Shi et al, 2010 ; Liu et al, 2013 ; Wang et al, 2017 ; Lisek et al, 2020 ). Although no reports are available for immature neurons, data from the adult brain suggest that ketamine may interfere with the assembly of local NMDAR/PSD-95/PMCA densities at the synaptic membrane, concentrating PMCA within Ca 2+ entry zones (Lisek et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%